'Polycation' modified PVDF based antibacterial and antifouling membranes and 'point-of-use supports' for sustainable and effective water decontamination. (December 2020) - Samantaray, Paresh Kumar; Kumar, Saurabh; Bose, Suryasarathi
Highlights: Polycation modified PVDF membranes for antibacterial and antifouling applications. The blend membranes showed more than 3 log fold reduction in bacterial colonies. The ceramic support coated with the polycations showed 6 log fold reduction in bacterial colonies. Polycation modified ceramic supports showed good dye adsorption. Point of use application for water decontamination was demonstrated. Abstract: Research concerning the design and development of non-leaching antibacterial agents for quick water decontamination is in great demand for their effective re-use and minimizing biocide contamination in water. Herein, we have synthesized two bactericidal polymers based on guanidine backbone (henceforth called GN) and sulphonium backbone (henceforth called SP). We explored their uniqueness in deriving polyvinylidene fluoride (PVDF) based blend membranes which are foul resistant and bactericidal. Besides, the potential of these polycations in point-of-use applications was explored by coating them on porous ceramic supports. The chemical structures of these polymers were investigated via Fourier Transformation Infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and 1 H nuclear magnetic resonance (NMR). The bactericidal action was tested against Escherichia coli ( E.coli ATCC 25922) and Staphylococcus aureus ( S.aureus ATCC 25923) based model strains. The blend membranes showed more than a 3-log reduction of bacterial colonies for both the strains and 6-log reduction in the case of ceramic supports coated with GN and SP. This was further corroborated with intracellular reactive oxygen species (ROS) measurements. The non-leaching nature of these biocides was confirmed by inductively coupled plasma optical emission spectroscopy (ICP-OES) analysis. The antifouling nature of blend membranes with GN and SP polymers was demonstrated using Bovine serum albumin as model foulant. Further, the unique polymers, when coated on ceramic supports, showed good dye adsorption for methyl orange as model dye pollutants owing to their electrostatic interactions with the dye.